Positron annihilation spectroscopic characterization of defects in wide band gap oxide semiconductors. (29th March 2017) - Sarkar, A; Luitel, Homnath; Gogurla, N; Sanyal, D
Abstract: Annealing effect of granular ZnO has been studied by Doppler broadened electron positron annihilated γ -ray (0.511 MeV) line shape measurement. Ratio curve analysis shows that granular ZnO samples contain both Zn and O vacancies. Such defects exist as agglomerates of several vacancies and start to recover above 400 °C annealing. It has also been observed that due to annealing temperature difference of 125 °C (from 325 °C to 450 °C), huge change occurs in low temperature photoluminescence (PL) of ZnO. Significant reduction of free to bound (FB) transition ~3.315 eV is observed for increasing the annealing temperature. It has been conjectured that ~3.315 eV PL in ZnO is related to particular decoration (unknown) of both Zn and O vacancies. The methodology of revealing defect-property correlation as employed here can also be applied to other types of semiconductors.